The impact, effectiveness and outcomes of targeted screening thresholds for programmatic latent tuberculosis infection testing in HIV. (15th November 2022) - White, Helena A.; Baggaley, Rebecca F.; Okhai, Hajra; Patel, Hemu; Stephenson, Iain; Bodimeade, Chris; Wiselka, Martin J.; Pareek, Manish
Abstract : Background: Screening and treatment for latent tuberculosis infection (LTBI) are key for TB control. In the UK, the National Institute for Health and Care Excellence (NICE) and the British HIV Association (BHIVA) give conflicting guidance on which groups of people with HIV (PWH) should be screened, and previous national analysis demonstrated heterogeneity in how guidance is applied. There is an urgent need for a firmer clinical effectiveness evidence base on which to build screening policy. Methods: We conducted a systematic, programmatic LTBI-screening intervention for all PWH receiving care in Leicester, UK. We compared yields (percentage IGRA positive) and number of tests required when applying the NICE and BHIVA testing strategies, as well as strategies targeting screening by TB incidence in patients' countries of birth. Results: Of 1053 PWH tested, 118 were IGRA-positive (11.2%). Positivity was associated with higher TB incidence in country-of-birth [adjusted odds ratio, 50–149 cases compared with <50 cases/100 000: 11.6; 95% confidence interval (CI) 4.79–28.10)]. There was high testing uptake (1053/1069, 98.5%). Appropriate chemoprophylaxis was commenced in 100 of 117 (85.5%) patients diagnosed with LTBI, of whom 96 of 100 (96.0%) completed treatment. Delivering targeted testing to PWH from countries with TB incidence greater than 150 per 100 000 population or any sub-Saharan African country, would have correctly identified 89.8% of all LTBI cases while cutting tests required by 46.1% compared with NICE guidance, performing as well as BHIVA 2018 guidance. Conclusion: Targeting screening to higher risk PWH increases yield and reduces the number requiring testing. Our proposed 'PWH-LTBI streamlined guidance' offers a simplified approach, with the potential to improve national LTBI-screening implementation.